Financing improvements and expansion : a case of the Sunnyhill Health & Racquet Club - Chard, Chris; McCrory, Liam; Spence, Kirsty (London : Human Kinetics, Inc., 2020)
The Sunnyhill Health & Racquet Club (SHRC) is a very small, private, volunteer-run, not-for-profit club located on a swath of prime real estate in the heart of a wealthy community in Sunnyhill Township. At the behest of the club's board, SHRC President David Wilson has been tasked with developing financing strategies to address the current (perceived) shortcomings of the club. Like he did for decades working in Post Office Square, in Boston's Financial District, Wilson knew he had to (1) understand the current financial capacity of SHRC, (2) discern the members' desire for financial contribution, and (3) develop financing options. Here, strategies to finance improvements to the club include debt utilization (and the necessary servicing of any debt commitments), one-time capital injections through the disposition of club property, and/or enhanced revenue generation. Developing strategies in an environment of disparate stakeholder goals provides additional challenges for Wilson.
Originally Published InChard, C., McCrory, L., & Spence, K. (2020). Financing Improvements and Expansion: A Case of the Sunnyhill Health & Racquet Club. Case Studies in Sports Management, 9(1), 12-19.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Business enterprises -- Finance